Neural signatures of naming retrieval: Theta and Alpha oscillatory dynamics functionally dissociate objects, people and places - Souza, C.; Carmo, J. C.; Ennahli, K.; Garrido, M. V. (Cognitive Neuropsychology)
This study examined Alpha and Theta oscillations in picture-naming retrieval of common objects, famous people and well-known places to investigate the distinct memory processes involved in retrieving these semantic categories. Thirty-two adults participated in a picture-naming task manipulating the Objects, Peopleand Places categories. EEG recordings were obtained during the entire task. Morlet wavelets were extracted for each band and condition across different time-bins. The behavioural results indicated lower naming precision for People, although naming Places was still more challenging than naming Objects. Electrophysiological results revealed functionally dissociable Theta and Alpha oscillation patterns across categories, possibly derived from their different contextual requirements. Places (long-lasting Theta synchronicity) differed symmetrically from Objects (long-lasting Alpha desynchronization). Places also partially differed from People, with the latter eliciting early but transient Theta synchronization and a subsequent desynchronization in Alpha. These findings may inform models of declarative memory interactions and encourage innovative approaches to assessment and intervention.